Faktor-Faktor Yang Mempengaruhi Nilai Tunggakan Kredit pada Program Pemberdayaan Ekonomi Masyarakat Pesisir di Kabupaten Indramayu - Alia Asmara (Jurnal Ilmu Pertanian Indonesia, 2007)
The objectives of this study were to analyze the income level of household, and to analyze the factors which influential non performance loan. This was a case study with purposive sampling method. The analysis comprised of income analysis, and econometric model. The results showed that the beneficiaries were in productive age, the educational level was relatively low, the average number of family member was 4 persons. The occupation of the user group community household mostly was fisherman with about 20 years experience. The major constraint of fisherman was the limited funding source. The income level of household was vary and the highest on marketing was about Rp 1,556,250/month. The factors that caused non-performing of loan return were the amount of loan and the level of education.Keywords: user group community household; income level; and non performance loan